Potential for codends with shortened lastridge ropes to replace mandated selection devices in demersal trawl fisheries - Sistiaga, Manu; Brinkhof, Jesse; Herrmann, Bent; Larsen, Roger B.; Grimaldo, Eduardo; Cerbule, Kristine; Brinkhof, Ilmar; Jørgensen, Terje (Canadian Journal of Fisheries and Aquatic Sciences, 2021)
In many trawl fisheries, codend size selectivity is supplemented by adding selection devices to the gear. In the Barents Sea gadoid fishery, combining diamond mesh codends with sorting grids is compulsory. However, the use of grids increases the costs and complexity of the gear, causing discontent among fishermen and prompting researchers to seek alternative solutions. Lastridge ropes are ropes attached to the selvedges of the codend. In this study, we tested the effect of shortening the lastridge ropes of two diamond mesh codends with different mesh sizes on the size selectivity of cod ( Gadus morhua ), haddock ( Melanogramus aeglefinnus ), and redfish ( Sebastes spp.). Shortening the lastridge ropes by 15% increased the mesh opening during the fishing process, which significantly improved the size-selective properties of the codends. Further, the L50 values were always higher for the codends in the short lastridge configuration. Therefore, codends with shortened lastridge ropes may be a simpler alternative to sorting grids in this fishery, and they may be applicable to many other fisheries in which additional selection devices are used.